Identifikasi Potensi Longsor Berbasis Sistem Informasi Geografis di Kecamatan Sembalun Kabupaten Lombok Timur - Baiq Tria Maulidasih; Bustan Bustan; Sukartono Sukartono (Journal of Soil Quality and Management, 2022)
This study aims to assess and map the spatial potential of landslides based on a geographic information system in Sembalun District. Field surveys were carried out from May to July 2020 on a land area of ​​18,318.45 Ha. Field observations include land characteristics, climatic characteristics (rainfall), soil properties in various types of land use. (shrubs, plantations, open land, dry land agriculture, residential and industrial areas, primary and secondary dryland forest. Soil sampling at a depth of 0-15 cm is carried out in a composite manner at 16 sampling points to determine soil properties, namely permeability, texture, structure and status of soil organic matter Data processing (slope, rainfall, geology, land use and erodibility) for the mapping process in the form ofshapefileand generate landslide prone maps from the overlay process. Landslide potential estimation using the method specified by Directorate of Volcanology and Geological Disaster Mitigation/DVMBG (2004). Score = (30% x rainfall class factor) + (20% x geology) + (20% x Erodibility class factor) + (15% x land use) + (15% x slope class factor). The results showed that around 32% (5,901.53 Ha) of the area of ​​Sembalun Subdistrict were in a high vulnerability status to landslide potential, 49% (8,911.39 Ha) were at moderate vulnerability status and 19% (3,505.71 Ha) had low vulnerability. The variables of erodibility and slope are the variables that show the most significant contribution to the potential for landslides in the area.